2001
DOI: 10.1055/s-2001-14077
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic Therapy in Children- Clinical Experiences with Recombinant Tissue-Plasminogen Activator

Abstract: For the improvement of thrombolytic therapy with recombinant tissue-plasminogen activator (rt-PA) in children, more clinical data are needed. We retrospectively analyzed the clinical course of 20 patients (age ranging from 1 day to 16 years) with venous thrombosis (n = 16), arterial thrombosis (n = 2), and purpura fulminans by meningococcosis (n = 2). The venous thromboses were localized in the iliac-femoral veins (n = 9), brachiocephalic-jugular-subclavian veins (n = 6), and the superior caval vein (n = 1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 13 publications
3
27
0
Order By: Relevance
“…The use of t-PA in adult practice for the treatment of pulmonary embolism, deep vein thrombosis, and acute myocardial infarction has been extensively reported. However, information regarding its use in childhood and infancy is limited [14] and most reports group arterial and venous thrombosis in a diverse age range together [15]. Regimens in use for children have, in the main, been extrapolated from adult data [16].…”
Section: Discussionmentioning
confidence: 98%
“…The use of t-PA in adult practice for the treatment of pulmonary embolism, deep vein thrombosis, and acute myocardial infarction has been extensively reported. However, information regarding its use in childhood and infancy is limited [14] and most reports group arterial and venous thrombosis in a diverse age range together [15]. Regimens in use for children have, in the main, been extrapolated from adult data [16].…”
Section: Discussionmentioning
confidence: 98%
“…Two retrospective case series of children with arterial and venous thrombosis studied the efficacy of thrombolysis with tissue plasminogen activator in terms of clot resolution. They showed complete clot resolution in 55-65% of children, partial resolution in 5-20%, and no effect in 15-40% (84,85). Thrombolytic agents are used commonly for arterial thrombosis in children, and to unblock central venous lines (57).…”
Section: Thrombolytic Therapymentioning
confidence: 97%
“…In medical treatment, heparin or fibrinolytic agents are used. Knöfler et al (16) reported that fibrinolytic t-PA was efficient and safe when used at an appropriate dose in the treatment of thrombosis. Surgical treatment is performed successfully in organized and calcified partial arcus aorta thrombosis without harming the other vessels.…”
Section: Discussionmentioning
confidence: 99%